2021
DOI: 10.1073/pnas.2114347118
|View full text |Cite
|
Sign up to set email alerts
|

An endoplasmic reticulum–localized cytochrome b 5 regulates high-affinity K + transport in response to salt stress in rice

Abstract: Potassium (K+) is an essential element for growth and development in both animals and plants, while high levels of environmental sodium (Na+) represent a threat to most plants. The uptake of K+ from high-saline environments is an essential mechanism to maintain intracellular K+/Na+ homeostasis, which can help reduce toxicity caused by Na+ accumulation, thereby improving the salt tolerance of plants. However, the mechanisms and regulation of K+-uptake during salt stress remain poorly understood. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…The predominant toxic ion is Na + because it inhibits K + absorption, and thus, maintaining a high K + /Na + ratio is important to improve salt tolerance in glycophytic plants (Hauser and Horie, 2010 ; Ismail and Horie, 2017 ). Increasing K + uptake and decreasing K + efflux are two major strategies to retain K + in glycophytic plants under salt stress (Hauser and Horie, 2010 ; Song et al, 2021 ). In this study, SKC and SDW were correlated.…”
Section: Discussionmentioning
confidence: 99%
“…The predominant toxic ion is Na + because it inhibits K + absorption, and thus, maintaining a high K + /Na + ratio is important to improve salt tolerance in glycophytic plants (Hauser and Horie, 2010 ; Ismail and Horie, 2017 ). Increasing K + uptake and decreasing K + efflux are two major strategies to retain K + in glycophytic plants under salt stress (Hauser and Horie, 2010 ; Song et al, 2021 ). In this study, SKC and SDW were correlated.…”
Section: Discussionmentioning
confidence: 99%
“…The downregulated expression of GhCIPK23 might participate in reducing Na + accumulation and balancing K + /Na + homeostasis under salt stress in upland cotton. Recent research shows that potassium signaling has been shown to act as a key determinant of plant salinity tolerance [ 40 , 41 , 42 , 43 ]. However, it is unclear whether GhCIPK23 may also be involved in K + uptake by plant roots under high sodium conditions, and the function of GhCIPK23 in regulating Na + and K + homeostasis needs to be addressed in future research.…”
Section: Discussionmentioning
confidence: 99%
“…The CDS of OsGF14b and OsPLC1 were respectively cloned to pCAMBIA1300‐cLUC and pCAMBIA1300‐nLUC using primers OsGF14b‐cLUC‐F/R and OsPLC1‐nLUC‐F/R (Table ). LCI analyses were performed as described previously (Chen et al, 2008; Han et al, 2015; Song et al, 2021). In brief, tobacco leaves were agroinfiltrated by the GV3101 containing different combinations, including OsGF14b ‐cLUC/ OsPLC1 ‐nLUC, OsGF14b ‐cLUC/nLUC, cLUC/ OsPLC1 ‐nLUC, or nLUC/cLUC.…”
Section: Methodsmentioning
confidence: 99%